HUBUNGAN STIGMA MASYARAKAT DENGAN PENERIMAAN MASYARAKAT TERHADAP ORANG DENGAN GANGGUAN JIWA - Yulita, Nepta; Nauli, Fathra Annis; Erwin, Erwin (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
Public acceptance of people with mental disorders (ODGJ) functions for the recovery process and prevents recurrence of ODGJ in the community, community stigma is one of the factors that can affect people with mental disorders being rejected or accepted in the community. This study aimed to determine whether there is a relationship between community stigma and community acceptance of ODGJ. This study uses a descriptive correlation design and a cross sectional. The research sample was 99 respondents who were taken based on the inclusion criteria using cluster sampling technique which a respondent taken from representatives of each family head (KK) who lived in the same RT with ODGJ. The analysis used is bivariate analysis using chi-square. Of the 99 respondents, community stigma showed 52 respondents (52,5%) with low stigma category, and public acceptance showed 56 respondents (56,6%) with good acceptance category with p value 0,000. It can be concluded that there is a significant relationship between community stigma and public acceptance of ODGJ.